Teknik Penyusunan Program Kerja Pelaksanaan Anggaran di Sektor Pendidikan - Basri Basri; Siradjuddin Siradjuddin; Alwan Suban (Fusshilat : Jurnal Studi Pendidikan dan Keislaman, 2025)
The preparation of a work program for educational budget implementation is a strategic step in managing financial resources to achieve educational goals. Effective budget management plays a crucial role in ensuring the availability of quality educational facilities and services. This article discusses seven key aspects of educational budget preparation, namely routine budgets, development budgets, budget determination, expedited work completion through cash programs, program cost analysis, and the preparation of unit costs for routine and development budgets. The routine budget covers daily operational needs, such as salary payments, stationery procurement, and facility maintenance, which are prepared based on an inventory of needs and priority setting. Meanwhile, the development budget focuses on long-term projects, such as renovations and new facility procurements. Budget determination is carried out by referring to data-based educational needs and involving stakeholders to ensure transparency. In addition, a cash program strategy is implemented to accelerate work completion through timely fund management. Program cost analysis helps evaluate the effectiveness of fund allocation by comparing benefits and costs and identifying potential inefficiencies. The preparation of unit costs, both for routine and development budgets, considers market price standards and the specific needs of each component. Each stage is designed to ensure transparent, efficient, and targeted budget management. With thorough planning and active involvement from various parties, the educational budget can be allocated optimally to create a conducive learning environment. This article is expected to serve as a practical guide for policymakers and educational practitioners in enhancing accountability and financial management quality in the education sector, thereby supporting the sustainable achievement of national educational goals.